Comparison of methodological quality of positive versus negative comparative studies published in Indian medical journals: a systematic review. Issue 6 (24th June 2015) - Charan, Jaykaran; Chaudhari, Mayur; Jackson, Ryan; Mhaskar, Rahul; Reljic, Tea; Kumar, Ambuj
Abstract : Objectives: Published negative studies should have the same rigour of methodological quality as studies with positive findings. However, the methodological quality of negative versus positive studies is not known. The objective was to assess the reported methodological quality of positive versus negative studies published in Indian medical journals. Design: A systematic review (SR) was performed of all comparative studies published in Indian medical journals with a clinical science focus and impact factor >1 between 2011 and 2013. The methodological quality of randomised controlled trials (RCTs) was assessed using the Cochrane risk of bias tool, and the Newcastle-Ottawa scale for observational studies. The results were considered positive if the primary outcome was statistically significant and negative otherwise. When the primary outcome was not specified, we used data on the first outcome reported in the history followed by the results section. Differences in various methodological quality domains between positive versus negative studies were assessed by Fisher's exact test. Results: Seven journals with 259 comparative studies were included in this SR. 24% (63/259) were RCTs, 24% (63/259) cohort studies, and 49% (128/259) case–control studies. 53% (137/259) of studies explicitly reported the primary outcome. Five studies did not report sufficient data to enable us to determine if results were positive or negative. Statistical significance was determined by p value in 78.3% (199/254), CI in 2.8% (7/254), both p value and CI in 11.8% (30/254), and only descriptive in 6.3% (16/254) of studies. The overall methodological quality was poor and no statistically significant differences between reporting of methodological quality were detected between studies with positive versus negative findings. Conclusions: There was no difference in the reported methodological quality of positive versus negative studies. However, the uneven reporting of positive versus negative studies (72% vs 28%) indicates a publication bias in Indian medical journals with an impact factor of >1.